IMPROVING STUDENTS’ READING COMPREHENSION SKILLS BY USING SQ3R (SURVEY, QUESTION, READ, RECALL, REVIEW) TECHNIQUE OF TENTH GRADE AT SMA NEGERI 1 REJOSO - Ani Nur Azizah; Triana Wuri Cahyanti (Universitas PGRI Mpu Sindok, 2025)
Indonesian students currently have a low level of literacy. Indonesia's literacy score in PISA 2022 dropped from 371 to 359. It is indicated that they have difficulty in gaining understanding from the text they read, it makes them less interested in reading activities, especially reading English texts. The objectives of this study are to find out the significant difference in students' reading comprehension skill before and after using SQ3R technique. This research is a quasi experimental research one group pre-test post-test. This research was conducted at SMA Negeri 1 Rejoso by using the population of all tenth grade namely 321 students, the sample used was class X-8 with 34 students. The sampling technique used non-probability sampling type convenience sampling. Data collection used tests.The data analysis technique used is descriptive statistics and inferential statistics t-test. Based on the results of the pre-test showed an average value of 46.76 with a low category. While the results of the post-test showed an increase with an average value of 85,29. From the t-test calculation results obtained tcount=19,06 >ttable=1,692 with a significant level of 5% with dk=33, so that H0 is rejected and Ha is accepted. So that